From us to me: cultural value changes from collectivism to individualism in Chinese commercials - Zhao, Jingyan (Kansas State University, 2017)
China’s society has been changing since 1979, when the open-door policy was implemented. Many great events in politics, economy and culture have brought lots of diversities to the Chinese younger generation who were born after 1979. These diversities have led to a cultural value change from collectivism to individualism among this generation (Cao, 2009; Sun & Wang, 2010; Moore, 2005). Cultivation analysis theory may be appropriate to explain this phenomenon as the open-door policy allowed American and European TV programs and other media products come into China. Effective advertising should cater to its audience in order to effectively persuade them to purchase its merchandise or service (Zhang & Harwood, 2004; Chang, 2006). If the cultural value of the Chinese younger generation has changed, it may be reflected in the commercial content of successful advertisers. This research conducted a content analysis of Chinese commercials, comparing the commercial contents in recent years to approximately ten years ago. It examined if the individualistic factors were more frequently showed in the commercials in recent years than approximately ten years ago, with the consideration to merchandise type and production place. Research results exhibited an increase of individualism revealing in Chinese commercials from approximately 2006 to 2016.
Keywords: Chinese advertising; Cultural value; Individualism and collectivism; Chinese younger generation